(The impact of training on the production efficiency of the workers of Siga Companyfor the period from (2000 – 2010 - Yahya, Hamza Abdullah Abdul Rahman (Journal of Economic, Administrative and Legal Sciences, 2018)
The study aimed at finding out the impact of training on the production efficiency of the workers of Siga Company for the period from(2000 – 2010) The study was based on basic questions related to the study. Is there a relationship between training and (productive efficiency، job satisfaction، keeping the human cadres) The study found the following results، training achieves an important objective which is the promotion and development of the capacities of individual .There is deficiency in the planning of training because of the lack of awareness of the training problems .There is no training manual the current irritation is that training is beneficial in any case .Training leads to the increase of productivity .good relation between superiors and subordinates are the most important factors of keeping human cadres، Training leads to the increase of job satisfaction. Based on these findings، the study recommended، The design of the training programmers must be planned according to scientific studies and plans، The training plans must be drawn according to an appropriate and modern methods so as to respond to the training reeds، The training process mast be evaluated periodically، The superiors must treat their subordinates by good relation، There is need for continuous training so as to increase productivity، There is need for continuous training so as to increase the employees job satisfaction.